ENVIRONMENTAL STUDY OF NEW EARLY-MATURING BARLEY LINES - O. B. Batakova; V. A. Korelina; N. V. Ivanova; A. V. Anisimova; O. N. Kovaleva (Труды по прикладной ботанике, генетике и селекции)
Early-maturing lines L-1610 and L-1611 developed and selected as high-yielding at the Leningrad Research Institute of Agriculture "Belogorka" were studied at Kotlas Breeding Experimental Station (Arkhangelsk region). As the result of the study in Kotlas, line L-1610 was identified as early-maturing (76-80 days), high-yielding (5.6 t/ga), with large grain (1000 grain weight: 51.3 g), and high resistance to lodging (9-7 points). Due to its sensitivity to lodging and unstable productivity in some years, line L-1611 was removed from the test.